(untitled) (Research, Society and Development, 2021)
To improve healthcare services with a focus on quality and safety, it is necessary that concrete, profound, practical, and relatively simple changes occur. These transformations are possible, and one of the strategies that can be used is the lean methodology. The study aimed to analyze the impact of the Lean methodology for the safety of hospitalized patients. The research is descriptive, of the integrative literature review type. The search was conducted between September and November 2019, by consulting the databases: MEDLINE/PubMed, LILACS, BDENF and IBECS. The results after analysis were grouped into two categories: 1) Use of Lean methodology to improve management processes in health services; 2) Lean methodology as a tool to improve care processes and patient safety. The studies analyzed showed that the Lean methodology impacts the quality of care, demonstrating how a lean organization can promote improvements in management, care and clinical processes, and consequently patient safety.